DESIGNING SCHOOL INFORMATION SYSTEM OF GUPPI GALAWATI SENIOR HIGH SCHOOL IN SORONG REGENCY - Iriene Surya Rajagukguk; Dewi Astuti (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2021)
At present the school is trying to become an educational institution that is able to serve the community in the delivery of information, one of which is the GUPPI Salawati High School, Sorong Regency. So far, the information about school information is still done manually by using banners, brochures and the latest information is still posted on the announcement board, even having to come directly to the school to get information. The method used in the development and design of this system is the Waterfall Method. The purpose of designing this information system is to facilitate those who need information about Salawati GUPPI high school.